Investigating operational risk challenges faced by micro enterprise in Malaysia - Ismail, Rina Fadhilah Ismail; Md Yusoff, Noreena; Ab Samad, Nur Hayati; Maswesi Ahmad, Emmarelda (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Micro and small enterprises have emerged as a pivotal driving force behind Malaysia's economic growth, contributing significantly to its overall economic prosperity. In the contemporary landscape of the digital economy, effectively navigating the multifaceted challenges that beset these enterprises is of paramount importance to ensure their sustained survival and success in the competitive economic environment. Understanding these risks and addressing them appropriately is essential to safeguard the long-term prospects of micro and small enterprises. This research endeavours to shed light on the diverse challenges associated with managing potential operational risks within the context of micro and small enterprises situated in Kuala Selangor, Selangor, Malaysia. In-depth interviews were conducted with a carefully selected group of business owners operating within the geographical confines of Kuala Selangor. The insights and data gathered from these interviews provide a comprehensive perspective on the challenges faced by these enterprising individuals, as well as their perceptions of operational risk occurrences within the contemporary business environment. Furthermore, this study also takes cognizance of its own limitations and offers valuable recommendations for future research directions in this domain. By exploring the nuances of managing operational risks in micro and small enterprises, this research seeks to contribute to a deeper understanding of the intricate economic landscape in Malaysia and provide insights that can inform policy, strategy, and best practices for the benefit of these crucial economic contributors.